A synthetic differentiation circuit in Escherichia coli for suppressing mutant takeover - Glass, David S.; Bren, Anat; Vaisbourd, Elizabeth; Mayo, Avi; Alon, Uri (Cell, 2024)
Differentiation is crucial for multicellularity. However, it is inherently susceptible to mutant cells that fail to differentiate. These mutants outcompete normal cells by excessive self-renewal. It remains unclear what mechanisms can resist such mutant expansion. Here, we demonstrate a solution by engineering a synthetic differentiation circuit in Escherichia coli that selects against these mutants via a biphasic fitness strategy. The circuit provides tunable production of synthetic analogs of stem, progenitor, and differentiated cells. It resists mutations by coupling differentiation to the production of an essential enzyme, thereby disadvantaging non-differentiating mutants. The circuit selected for and maintained a positive differentiation rate in long-term evolution. Surprisingly, this rate remained constant across vast changes in growth conditions. We found that transit-amplifying cells (fast-growing progenitors) underlie this environmental robustness. Our results provide insight into the stability of differentiation and demonstrate a powerful method for engineering evolutionarily stable multicellular consortia. [Display omitted] •Synthetic E. coli differentiation produces a stem-progenitor-differentiated lineage•Cell-autonomous coupling to an essential trait suppresses differentiation mutants•Fast-growing progenitors provide environmentally robust biphasic differentiation•Fitness landscape engineering guides long-term, environmentally robust behavior Bacteria were engineered to produce analogs of stem, progenitor, and differentiated cells. Coupling differentiation to an essential trait generated a biphasic fitness landscape, suppressing mutant takeover and providing an environmentally robust differentiation rate.